The Influence of Cinema on Consumer Purchasing Behaviour: An Analysis of Age and Gender Differences - Vasu Patel; Abhi Rajkotiya; Lucky Mendpara; Netra Viramgama; Rahul Chauhan; Andino Maseleno (Greenation International Journal of Economics and Accounting, 2024)
This study explores the relationship between cinema and consumer Behaviour, focusing on how age and gender influence purchasing decisions after viewing movies. A total of 105 respondents from Ahmedabad, India, were surveyed using a structured questionnaire that assessed movie-watching habits, preferred platforms, and the impact of films on purchasing Behaviour. The data was analyzed using **SPSS** with **ANOVA (Analysis of Variance)** to examine the differences in Behaviours across different age groups and genders. The results revealed that while age significantly influenced whether respondents made purchases after seeing products in films, gender did not have a substantial effect on viewing habits or purchase decisions. The findings highlight the increasing influence of cinema, particularly among younger audiences, in shaping consumer preferences for products and services. The study suggests that the entertainment industry and marketers can benefit from a deeper understanding of these trends to better target consumer segments. Future research could explore the impact of cultural factors and digital media on these Behaviours.